Identification of Febuxostat as a New Strong ABCG2 Inhibitor: Potential Applications and Risks in Clinical Situations - Miyata, Hiroshi; Takada, Tappei; Toyoda, Yu; Matsuo, Hirotaka; Ichida, Kimiyoshi; Suzuki, Hiroshi (Frontiers in Pharmacology, 2016)
ATP-binding cassette transporter G2 (ABCG2) is a plasma membrane protein that regulates the pharmacokinetics of a variety of drugs and serum uric acid (SUA) levels in humans. Despite the pharmacological and physiological importance of this transporter, there is no clinically available drug that modulates ABCG2 function. Therefore, to identify such drugs, we investigated the effect of drugs that affect SUA levels on ABCG2 function. This strategy was based on the hypothesis that the changes of SUA levels might caused by interaction with ABCG2 since it is a physiologically important urate transporter. The results of the in vitro screening showed that 10 of 25 drugs investigated strongly inhibited the urate transport activity of ABCG2. Moreover, febuxostat was revealed to be the most promising candidate of all the potential ABCG2 inhibitors based on its potent inhibition at clinical concentrations; the half-maximal inhibitory concentration of febuxostat was lower than its maximum plasma unbound concentrations reported. Indeed, our in vivo study demonstrated that orally administered febuxostat inhibited the intestinal Abcg2 and, thereby, increased the intestinal absorption of an ABCG2 substrate sulfasalazine in wild-type mice, but not in Abcg2 knockout mice. These results suggest that febuxostat might inhibit human ABCG2 at a clinical dose. Furthermore, the results of this study lead to a proposed new application of febuxostat for enhancing the bioavailability of ABCG2 substrate drugs, named febuxostat-boosted therapy, and also imply the potential risk of adverse effects by drug-drug interactions that could occur between febuxostat and ABCG2 substrate drugs.